Three dimensional printed macroporous polylactic acid/hydroxyapatite composite scaffolds for promoting bone formation in a critical-size rat calvarial defect model. Issue 1 (1st January 2016) - Zhang, Haifeng; Mao, Xiyuan; Du, Zijing; Jiang, Wenbo; Han, Xiuguo; Zhao, Danyang; Han, Dong; Li, Qingfeng
Abstract: We have explored the applicability of printed scaffold by comparing osteogenic ability and biodegradation property of three resorbable biomaterials. A polylactic acid/hydroxyapatite (PLA/HA) composite with a pore size of 500 μm and 60% porosity was fabricated by three-dimensional printing. Three-dimensional printed PLA/HA, β-tricalcium phosphate (β-TCP) and partially demineralized bone matrix (DBM) seeded with bone marrow stromal cells (BMSCs) were evaluated by cell adhesion, proliferation, alkaline phosphatase activity and osteogenic gene expression of osteopontin (OPN) and collagen type I (COL-1). Moreover, the biocompatibility, bone repairing capacity and degradation in three different bone substitute materials were estimated using a critical-size rat calvarial defect model in vivo . The defects were evaluated by micro-computed tomography and histological analysis at four and eight weeks after surgery, respectively. The results showed that each of the studied scaffolds had its own specific merits and drawbacks. Three-dimensional printed PLA/HA scaffolds possessed good biocompatibility and stimulated BMSC cell proliferation and differentiation to osteogenic cells. The outcomes in vivo revealed that 3D printed PLA/HA scaffolds had good osteogenic capability and biodegradation activity with no difference in inflammation reaction. Therefore, 3D printed PLA/HA scaffolds have potential applications in bone tissue engineering and may be used as graft substitutes in reconstructive surgery. Abstract : UF0001